Coherent coupling of molecular spins with microwave photons in planar superconducting resonators. Issue 1 (1st January 2018) - Bonizzoni, Claudio; Ghirri, Alberto; Affronte, Marco
Abstract: Within the quest for solid state quantum systems to be used for fundamental as well as applied research, molecular spins have recently emerged as a versatile platform with interesting performances in terms of quantum coherence and correlation. Molecular units provide well defined environment to electronic spins and they represent elementary bricks for complex nano-architectures and nano-devices. Here we review our recent efforts and results on their efficient integration in circuit Quantum ElectroDynamics and, more specifically, in reaching their coherent coupling with microwave photons in planar resonators. To monitor molecular spin performances over a wide temperature and magnetic field range we have first developed microwave planar resonators made of high T c superconductors, obtaining excellent performances up to liquid Nitrogen temperature and in magnetic fields up to 7 Tesla. Ensembles of different molecular spins systems are then systematically tested. The regime of high spin-photon cooperativity is achieved with molecular spins diluted in non-magnetic matrix at 0.5 K, while the strong coupling regime is observed with concentrated samples of organic radicals up to 50 K. The possibility to create coherent states among distinct spin ensembles is further explored in similar spectroscopic experiments. These results show that molecular spins can be efficiently integrated in quantum devices. Abstract :